Juvenile dermatomyositis: association between nail fold capillary end row loop- area under the curve- and disease damage indicators - Amer Khojah; Gabrielle Morgan; Marisa S. Klein-Gitelman; Lauren M. Pachman (BMC, 2023)
Abstract Background Juvenile Dermatomyositis (JDM) is a rare autoimmune disease characterized by skin and muscle inflammation. The loss of nail fold capillary end row loops (ERL) is evidence of small vessel involvement in JDM. This study aimed to examine the specific association of ERL over the disease course with evidence of JDM disease damage. Methods We analyzed data from 68 initially treatment-naïve JDM children who had been observed for at least five years with multiple ERL density assessments. The JDM disease course were categorized into monocyclic short, monocyclic long, polycyclic, and chronic. The ERL capillary count was cumulatively evaluated using the area under the curve (AUC) method. Results The mean ERL density for the treatment-naive JDM was significantly lower than that of their healthy age-matched controls (4.8 ± 1.6 /mm vs. 7.9 ± 0.9 /mm; p < 0.0001). The ERL AUC was significantly lower in children with a chronic disease course compared to those with a monocyclic short (p = 0.001) or monocyclic long disease course (p = 0.013). JDM patients with lipodystrophy had lower ERL AUC than those without lipodystrophy (p = 0.04). There was no association between ERL AUC and calcifications or fractures. Conclusion Persistently decreased ERL capillary density, reflected by low ERL AUC, is associated with a chronic disease course and lipodystrophy in JDM. Despite medical therapy, the mean ERL count remained below normal even after five years, particularly in polycyclic and chronic cases. It is not clear that restoring normal capillary density is currently feasible in children with JDM.